2011
DOI: 10.1016/j.ijrobp.2011.06.787
|View full text |Cite
|
Sign up to set email alerts
|

Validation that Metabolic Tumor Volume Predicts Outcome in Head and Neck Cancer

Abstract: Purpose-We have previously reported that metabolic tumor volume (MTV) obtained from pretreatment FDG PET/CT predicted outcome in patients with head-and-neck cancer (HNC). The purpose of this study is to validate these results on an independent dataset, determine if the primary tumor or nodal MTV drives this correlation, and explore the interaction with p16 INK4a status as a surrogate marker for HPV.Methods and Materials-The validation dataset in this study included 83 patients with squamous cell HNC who had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…A possible limitation is that it represents the highest voxel value within a lesion. In this direction a growing body of literature has started to analyze more in deep SUVmean and metabolic tumor volume (MTV) [25,[30][31][32]. Actually, SUVmean represents the average of the intensity of uptake within a designated region of interest and MTV reflects the volume of tumor tissue with increased metabolic activity on PET.…”
Section: Discussionmentioning
confidence: 99%
“…A possible limitation is that it represents the highest voxel value within a lesion. In this direction a growing body of literature has started to analyze more in deep SUVmean and metabolic tumor volume (MTV) [25,[30][31][32]. Actually, SUVmean represents the average of the intensity of uptake within a designated region of interest and MTV reflects the volume of tumor tissue with increased metabolic activity on PET.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of primary tumor SUVmax in patients with head and neck cancer remains controversial, and many reports have indicated that it has positive [8] or negative [9] associations with outcome. Allal et al [8] demonstrated that a primary tumor SUV exceeding 4.76 posed a greater risk of poor outcome in 120 patients with various head and neck cancers including those of the oropharynx (n = 46), oral cavity (n = 32), larynx (n = 26), hypopharynx (n = 13), or unknown primary (n = 3) managed by radiotherapy or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several segmentation methods have been proposed for the analysis of PET images in patients with head and neck malignancies, but no widely accepted guidelines exist. Although a fixed threshold of 50 % of the maximum SUV (SUV max 50 %) may be unsuitable for determining tumour volume in the presence of heterogeneous lesions [23], this threshold has been used successfully in head and neck cancer [24,25]. We selected this delineation method based on its availability and clinical usefulness.…”
Section: Pet/ct Image Analysismentioning
confidence: 99%